Efficient IDUA Gene Mutation Detection with Combined Use of dHPLC and Dried Blood Samples - Ribeiro, Diogo (ISRN Mol Biol, 2013)
Objectives. Development of a simple mutation directed method in order to allow lowering the cost of mutation testing using an easily obtainable biological material. Assessment of the feasibility of such method was tested using a GC-rich amplicon. Design and Methods. A method of denaturing high-performance liquid chromatography (dHPLC) was improved and implemented as a technique for the detection of variants in exon 9 of the IDUA gene. The optimized method was tested in 500 genomic DNA samples obtained from dried blood spots (DBS). Results. With this dHPLC approach it was possible to detect different variants, including the common p.Trp402Ter mutation in the IDUA gene. The high GC content did not interfere with the resolution and reliability of this technique, and discrimination of G-C transversions was also achieved. Conclusion. This PCR-based dHPLC method is proved to be a rapid, a sensitive, and an excellent option for screening numerous samples obtained from DBS. Furthermore, it resulted in the consistent detection of clearly distinguishable profiles of the common p.Trp402Ter IDUA mutation with an advantageous balance of cost and technical requirements.